BIMBINGAN KONSELING DALAM MENGATASI SIKAP INDISIPLINER SISWA DI SD NEGERI WINDUAJI 07 PAGUYANGAN BREBES - Astriani, Era (Jurnal Tawadhu, 2018)
In education both elementary, middle and upper level, counseling guidance is needed, especially in dealing with students' disciplinary attitudes. In dealing with disciplinary attitudes students a teacher guidance counseling has a different way because students who often perform disciplinary attitudes have different backgrounds there are those from broken home families so that students receive less attention.The purpose of this study is to find out how classroom guidance teachers at SD N Winduaji 07 handle students' disciplinary attitudes, motivate students not to violate the rules in school and students can hold the key to discipline to succeed the learning process.The results of this study indicate that the counseling tutor addresses the rest of the disciplinary in different ways, for the low class by approaching students who remain based on the assertiveness of the teacher counseling guidance such as disciplinary orders delivered to students either individually or in groups. For high-class students who often carry out disciplinary attitudes, the attitude of the teacher counseling guidance is different and has not used the word command but uses invitations and motivation and makes students as partners in individual or group guidance.Keywords: counseling guidance, disciplinary attitudes of students